Trending Topics in E-government, E-participation, and Social Media in the Crisis Era. - Garrote-Quintana, Alba; Urquía-Grande, Elena; Delgado Jalón, María Luisa (Administration & Society, 2025)
This study analyses three major research fields: citizens' e-government, e-participation, and social media use. It compares the distribution of publications and citation network structure. We use three bibliometric software tools (SciMAT, Citnet, and CiteSpace). The results indicate that social media is a growing research topic attracting increasing attention in the academic community. They also show that authors from the USA and China lead in number of publications. We found some common references to pioneers in the field and specific topics where the authors cite a predecessor in the research area, such as public value and antecedents of trust.